Design and development of undulating fin - Andre, Willy (2008)
Recently researchers and scientists have been more vocal than in the past in promoting an awareness to preserve environment. One of their main concerns is the sustainability of underwater ecology, especially marine environment, which is deteriorating due to extensive use of propellers. Imitating natural propulsion system (biomimetic) is an alternative to solve the concern mentioned above, which is to replace propellers. Thorough examination into the locomotion of living creatures reveals their oscillatory pattern. The research leads to the development of an environment friendly propulsion system, which mimics undulating fin of narrow-finned fish such as cuttlefish and knifefish.